1992
DOI: 10.1080/01635589209514198
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and anticarcinogenic effects of carotenoids and dietary palm oil

Abstract: Four carotenoids, canthaxanthin, beta-carotene, 8H-apo-beta-carotenal, and 8'-apo-beta-carotene methylester were tested for their ability to suppress the mutagenicity of 1-methyl-3-nitro-1-nitrosoguanidine and benzo[a]pyrene (BP) in Salmonella typhimurium tester strain TA 100. The anticarcinogenic efficacy of the four carotenoids was further assessed in the BP-induced forestomach tumor model in female Swiss mice. The effect of dietary palm oil was also examined in BP-induced neoplasia in the female Haffkine Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…Cryptoxanthin was reported to be more effective than b-carotene or canthaxanthin, while lycopene had no effect (He and Campbell, 1990). When either 1-methyl-3-nitro-1-nitrosoguanidine (MNNG) or benzo(a)pyrene (B(a)P) were used to initiate mutagenesis, b-carotene, canthaxanthin, b-apo-8 0 -carotenal and methylb-apo-8 0 -carotenoate all demonstrated a dose-dependent decrease in mutagenicity (Azuine et al, 1992). However, not all of these studies were supportive of a role for carotenoids as antimutagens.…”
Section: Antimutagenic Action In Bacteriamentioning
confidence: 97%
“…Cryptoxanthin was reported to be more effective than b-carotene or canthaxanthin, while lycopene had no effect (He and Campbell, 1990). When either 1-methyl-3-nitro-1-nitrosoguanidine (MNNG) or benzo(a)pyrene (B(a)P) were used to initiate mutagenesis, b-carotene, canthaxanthin, b-apo-8 0 -carotenal and methylb-apo-8 0 -carotenoate all demonstrated a dose-dependent decrease in mutagenicity (Azuine et al, 1992). However, not all of these studies were supportive of a role for carotenoids as antimutagens.…”
Section: Antimutagenic Action In Bacteriamentioning
confidence: 97%
“…Several studies in recent years have indicated that curcumin is a potent inhibitor of the initiation and tumor promotion of chemical carcinogen-induced tumor formation in mice and proliferation of animal muscle and epithelial cells [95][96][97][98].…”
Section: Iv41 Ptk Inhibitory Activity Of Curcuminmentioning
confidence: 99%
“…This review, however, summarizes the background information about lycopene and represents the most current knowledge with respect to its role in human health and disease. We have reported the manifold activities of carotenoids with reference to its antioxidant properties, anticarcinogenic activities and conversion into different retinoids (Azune et al 1992; Barua and Goswami 1977;Goswami and Barua 1981a, b, c;Goswami and Bhattacharya 1982;Goswami 1984Goswami , 1991Goswami , 2006Goswami and Sharma 2005;Goswami et al 1989Goswami et al , 1991Goswami et al , 1995Shah et al 1992;Aboobaker et al 1997). Several studies have been made on the carotenoids content and lycopene in particular from Indian fruits and vegetables (Bhaskarachary 2010;Bhaskarachary et al 2008).…”
mentioning
confidence: 93%